A new fossil species of Bolitophagini (Coleoptera: Tenebrionidae) from Baltic amber suggests the genus Eledonoprius Reitter is persistent in the Western Palaearctic since the Tertiary - Alekseev, Vitalii I.; Bukejs, Andris; Sontag, Elżbieta (Zootaxa, 2020)
The first fossil representative of Eledonoprius Reitter, E. incoronatus sp. nov., is described from Eocene Baltic amber. The genus is associated with old-growth forests in the modern Western Palaearctic Region and apparently has persistent in this Region since the Paleogene.